Molecular basis of host specificity in human pathogenic bacteria - Pan, Xiaolei (Nature Publishing Group, 2014)
Pathogenic bacteria display various levels of host specificity or tropism. While many bacteria can infect a wide range of hosts, certain bacteria have strict host selectivity for humans as obligate human pathogens. Understanding the genetic and molecular basis of host specificity in pathogenic bacteria is important for understanding pathogenic mechanisms, developing better animal models and designing new strategies and therapeutics for the control of microbial diseases. The molecular mechanisms of bacterial host specificity are much less understood than those of viral pathogens, in part due to the complexity of the molecular composition and cellular structure of bacterial cells. However, important progress has been made in identifying and characterizing molecular determinants of bacterial host specificity in the last two decades. It is now clear that the host specificity of bacterial pathogens is determined by multiple molecular interactions between the pathogens and their hosts. Furthermore, certain basic principles regarding the host specificity of bacterial pathogens have emerged from the existing literature. This review focuses on selected human pathogenic bacteria and our current understanding of their host specificity.